Análise do processo de diagnóstico e intervenção em crianças com deficiência auditiva em um serviço do município de São Paulo: identificação de barreiras e no fluxo - Rúpolo, Adrielle Cristina (2022)
Introduction: The diagnosis of hearing loss in children performed in the first months of life, with intervention, can be considered determining factors for the development of auditory skills and early language. The effective use and quality of the electronic device, speech therapy and family expectations and their implication with the important factors for the child's prediction, as well as aspects related to socioeconomic, cultural and academic. The Health Department organizes the flow of referral of babies and children with the hearing consultation so that the timely service with the beginning of the speech therapy intervention, and the adherence to its stages. However, intercurrences can happen during this process, hindering the child's development. Objective: The purpose of this research was to analyze the process of diagnosis and intervention of children with permanent hearing loss from a reference service in hearing health, identifying their barriers. Method: The research was carried out using data from medical records and scheduling data from children with hearing impairment diagnosed in a Specialized Rehabilitation Center. This study has a quantitative/qualitative descriptive character. The subjects were characterized from the demographic and audiological point of view. In the analysis, they were identified as diagnoses, between the process of diagnosis and intervention and as characteristics and follow-up of patients, in addition to audiological care. Results: Most of the subjects attended more than 75% of the appointments for the audiological diagnosis, but just over 40% of the families attended the sessions for the selection of hearing aids and speech therapy. The vast majority returned spontaneously to the service (84.09%), however, less than 30% attended within a time interval considered adequate for children, less than six months. A relationship was observed with the SII of the best ear, being scheduled for failure in universal screening, the grade of hearing loss and distance between the region of residence and the service in the time interval between the beginning of the therapy and the first follow-up. Conclusion: The results showed variability between subjects, and it was not possible to find statistical significance in the analysis performed. However, the analysis model of the three moments of the intervention process allowed us to find statistical trends that can help to improve the hearing health service for the population